Farmers’ education and perception on pesticide use and crop economies in Indian agriculture - M. Murugan1, M.B. Hiremath1,2* and K.G. Sreeja1, P.K. Shetty1, (Journal of Experimental Sciences, 2010)
Intensive survey involving 1039 farmers belonging to 28 districts in 12 Indian states was carried out in pesticide use predominant regions to study the influence of farmer’s awareness, education and practices related to pesticide use as well as Integrated Pest Management (IPM) measures. Data were collected through pre-tested schedules by trained field investigators and the data were analysed by suitable statistical package (SPSS). The results revealed that though overall consumption of pesticide decreased, the expenditure incurred on pesticides remained high. Most of the respondents in the surveyed area followed their own spraying schedules and pesticide doses to manage ever increasing insect pests and disease problems. More than 50 % of the respondents applied both single and cocktail pesticides to manage their crop pests. Greater number of the literate farmers had strong perception on the negative impacts of pesticides on soil, water, air and beneficial organisms. Only 20 % of the respondents obtained their information on plant protection aspect from the agricultural extension officer and the rest of 80% of the farmers used unreliable information in crop production of surveyed areas. The respondents in the study regions were of the opinion that chemical methods of pest control are very effective in combating serious pest infestation. In the study area it was observed that only 3 % of the respondents followed organic farming in a successful way. The total area under organic farming in India is negligible. There is a tremendous scope for agricultural extension activity through which stewardship can be achieved in these pesticide predominant regions. Nevertheless, costs on ever increasing safety measures for pesticide applicators would be an additional burden which is to be considered seriously under resource poor small and medium holding systems in India.